Analysis of The Potential of Turing Kayak Sports Tourism in Cimanuk River, Sumedang Regency - Rezky Purnama Putra; Rizal Ahmad Fauzi; Encep Sudirjo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research aims to analyze the potential for water sports tourism on the Cimanuk Parakan River, Sumedang Regency using kayak touring, kayak touring itself is a very interesting sport of course it also tests adrenaline in every activity, the method in this research uses qualitative with tourist participants, area managers local and touring kayak operators, the instrument used was MSPDM (Maketability, Sustainability, Participatory, and Disaster Mitigation) through interviews and data analysis documentation using the Nvivo12 software application. The results obtained from the Nvivo 12 software application are that kayak touring has the potential to be used as a water sports or recreational sports tourist attraction. conclusion from the research title Analysis of the potential for water sports tourism on the Cimanuk Parakan River, Sumedang Regency using kayak touring, it can be concluded that kayak touring is one of the water sports tourism which has the potential to become a sports tourism. because the water in the famous Cimanuk Parakan river will remain stable whether it is rainy or dry because it is accommodated by the Jati Gede Dam, this can raise the name of the Sumedang area and also improve the economy of the community in water sports tourist destinations like a tour.